Case Report: Falsely elevated PTH level in a young woman caused by immunoassay interference resulting from macro-PTH - Perruolo, Giuseppe; Santarpia, Lidia; Morelli, Cristina; Rendina, Domenico; Mormone, Federica; Ferraro, Giusy; Formisano, Pietro; Oriente, Francesco (Frontiers in Endocrinology, 2025)
Elevated parathyroid hormone (PTH) levels usually suggest an underlying parathyroid disorder. However, immunoassay interference, such as macro-PTH, can result in falsely elevated readings, leading to diagnostic inaccuracy. Here, we report the case of a 27-year-old woman with persistently elevated PTH levels despite normal serum calcium, phosphate, and vitamin D. Aside from a history of nephrolithiasis, the patient was asymptomatic and exhibited no parathyroid abnormalities detected on ultrasound, sestamibi scintigraphy, or choline positron emission tomography-computed tomography (PET-CT) scans. To investigate potential immunoassay interference, a polyethylene glycol (PEG) 6000 precipitation assay was performed, which showed a decrease of PTH levels from >1200 pg/mL to approximately 40 pg/mL, corresponding to a 97% reduction. To validate the specificity of this technique, the same procedure was conducted on sera from two patients with elevated PTH levels due to known parathyroid pathologies. PTH levels decreased from 771 to 271 pg/ml and 527 to 146 pg/ml, corresponding to 65 and 72% reduction, respectively. The following results indicated that the PEG precipitation primarily affected the macro-PTH in our patient’s sample while leaving intact PTH relatively unaffected in the control group. This report suggests that unexpectedly high PTH levels in the presence of otherwise normal laboratory values and imaging results could indicate the possibility of immunoassay interference. PEG 6000 precipitation is a valuable diagnostic tool for macro-PTH detection, although further refinement of immunoassay techniques may be needed to enhance the reliability of PTH measurements in clinical practice.